A Comprehensive Review of 4D Printing: State of the Arts, Opportunities, and Challenges - Aldawood, Faisal Khaled (Actuators, 2023)
Over the past decade, 3D printing technology has been leading the manufacturing revolution. A recent development in the field of 3D printing has added time as a fourth dimension to obtain 4D printing parts. A fabricated design created by 3D printing is static, whereas a design created by 4D printing is capable of altering its shape in response to environmental factors. The phrase “4D printing” was introduced by Tibbits in 2013, and 4D printing has since grown in popularity. Different smart materials, stimulus, and manufacturing methods have been published in the literature to promote this new technology. This review paper provides a description of 4D printing technology along with its features, benefits, limitations, and drawbacks. This paper also reviews a variety of 4D printing applications in fields such as electronics, renewable energy, aerospace, food, healthcare, and fashion wear. The review discusses gaps in the research, the current challenges in 4D printing, and the future of 4D printing.